Quick butt welding of steel sheets using the high-speed laser cladding method - Li, Yongjian; Liu, Xiaoting; Yan, Shixing; He, Peng (Frontiers in Materials, 2022)
Laser butt welding of thin steel sheet without filler material was widely used in many industry fields, however, to focus the small laser spot on the narrow gap between the sheets was very difficult during the laser butt welding process. In this study, a new method to weld thin steel sheet using high speed laser cladding technique was proposed. Thin stainless steel sheets with a thickness of 0.5mm were butt welded using high speed laser cladding process. The results illustrated that most of the specimens showed well joints without obvious cracks, pores and other defects. The joints were well formed even if the sheets were not spliced together obviously. The average tensile strength of the specimens was about 500 MPa, which is almost the same as that of the substrate. The results also showed that most of the failure were not happened in the weld position, which could be concluded that the strength of joints was higher than that of the substrate. The microstructure was determined using Optical microscope (OM) and Scanning electron microscopy (SEM). The results showed that it may be a good choice to use high speed laser cladding technique for the butt welding of thin stainless steel sheets.